Polymorphisms in the TGFB1 and IL2RA genes are associated with clinical forms of leprosy in Brazilian population - Camargo, Rodrigo Mendes de [UNESP]; Silva, Weber Laurentino da [UNESP]; Medeiros, Priscila [UNESP]; Fernandes Belone, Andrea de Faria; Pereira Latini, Ana Carla [UNESP] (Fundaco Oswaldo Cruz, 2018)
BACKGROUND Leprosy is a chronic infectious disease caused by Mycobacterium leprae, and compromises the skin and peripheral nerves. This disease has been classified as multibacillary (MB) or paucibacillary (PB) depending on the host immune response. Genetic epidemiology studies in leprosy have shown the influence of human genetic components on the disease outcomes. OBJECTIVES We conducted an association study for IL2RA and TGFBI genes with clinical forms of leprosy based on two case-control samples. These genes encode important molecules for the immunosuppressive activity of Treg cells and present differential expressions according to the clinical forms of leprosy. Furthermore, IL2RA is a positional candidate gene because it is located near the 10p13 chromosome region, presenting a linkage peak for PB leprosy. METHODS A total of 885 leprosy cases were included in the study; 406 cases from Rondonopolis County (start population), a hyperendemic region for leprosy in Brazil, and 479 cases from Sao Paulo state (replication population), which has lower epidemiological indexes for the disease. We tested 11 polymorphisms in the IL2RA gene and the missense variant rs1800470 in the TGFB1 gene. FINDINGS The AA genotype of rs2386841 in IL2RA was associated with the PB form in the start population. The AA genotype of rs1800470 in TGFBI was associated with the MB form in the start population, and this association was confirmed for the replication population. MAIN CONCLUSIONS We demonstrated, for the first time, an association data with the PB form for a gene located on chromosome 10. In addition, we reported the association of TGFBI gene with the MB form. Our results place these genes as candidates for validation and replication studies in leprosy polarisation.
Keywords: leprosy; genetic epidemiology; TGFB1; IL2RA; Tregs